2016
DOI: 10.1590/1678-4324-2016160102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Brycon hilarii in a Repopulation Program

Abstract: (0.2622 -0.2617). Results show that the wild population and the broodstock had high genetic variability and low genetic divergence; contrastingly, fingerlings showed mild genetic variability and great divergence when compared to other groups, indicating that they were not adequately constituted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
2
2
1
Order By: Relevance
“…The size of alleles produced by primers derived from the genus Brycon was similar to that in previous research , as B. hilarii (SANCHES & GALETTI, 2006;BIGNARDI et al, 2016) results are close to those observed by these authors and showed moderate genetic variability. The mean value of He was higher than the value of Ho, which likely inferred the significant deviation in the Hw, indicating a heterozygous deficit through the Fis coefficient in most of loci.…”
Section: Discussionsupporting
confidence: 89%
“…The size of alleles produced by primers derived from the genus Brycon was similar to that in previous research , as B. hilarii (SANCHES & GALETTI, 2006;BIGNARDI et al, 2016) results are close to those observed by these authors and showed moderate genetic variability. The mean value of He was higher than the value of Ho, which likely inferred the significant deviation in the Hw, indicating a heterozygous deficit through the Fis coefficient in most of loci.…”
Section: Discussionsupporting
confidence: 89%
“…In a study with natural populations of Prochilodus lineatus, Lopera- Barrero et al (2016b) found a variation of three to six alleles produced by the Par12 locus and three to five alleles produced by the Par80 locus. The number of alleles produced in our study was lower than that reported by Bignardi et al (2016) for Brycon hilarii using the loci Bh8, Bh13, and Bh16. The same applies to the primers Par80 and Cm1A8, which showed a lower ACTA AMAZONICA number of alleles than that found in the literature (Barbosa et al 2008;Lopera-Barrero et al 2016b;Santos et al 2009).…”
Section: Discussioncontrasting
confidence: 87%
“…Genetic analyzes of populations on a wider geographic scale will be necessary to estimate variability and the level of genetic structure in this species, and to evaluate the possibility of inbreeding in shoals, which would raise F IS values. The size of the alleles produced are close to the values reported by Bignardi et al (2016) for B. hilarii. The primer Bag22 also produced a similar size to that found by Araújo (2012) for B. amazonicus.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…number of alleles per locus was also similar to that reported in the cross-amplification in B. orbignyanus at some loci such as bom13 (cArmo et al, 2015;cAsTro et al 2017), bh13, bom5, andPar80 (cAsTro et al, 2017). contrarily, the number of alleles was lower relative to those reported from studies that used species-specific primers of B. opalinus and B. hilarii (bArroso et al, 2003;biGnArDi et al, 2016). other studies have demonstrated that the genus Prochilodus also has a high plasticity of microsatellite loci transfer (bArbosA et al, 2008;LoPerA-bArrero et al, 2016b), even among different genera, as shown by cAsTro et al 2017, who observed that Par80, the same loci amplified for B. gouldingi, showed crossamplification in B. orbignyanus.…”
Section: Discussionmentioning
confidence: 69%